PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PT BPR DANA NUSANTARA DI KOTA BATAM - Lis, Rustiana; Setiawan, Joko (SCIENTIA JOURNAL, 2019)
The issue of Compensation and Work Motivation for employees is a classic problem that must still be placed to get work productivity and Job Satisfaction for employees. By taking the title of research on the Effect of Compensation and Work Motivation on Employees of PT BPR Dana Nusantara in Batam City, to see the extent of the influence of these two variables on Employee Job Satisfaction. The research method used is to take a sample of 119 employees consisting of several divisions at BPR Dana Nusantara Batam. The Data Collection Technique used in this study was by interviewing directly and distributing randomly distributed questionnaires to employees of PT BPR Dana Nusantara in Batam City. Test the research data using Validity Test, Reliability Test, Normality Test, Determination Coefficient Test (R2), Partial T Test and Simultaneous F Test. From this study found results that Fcount is greater than Ftable and Thitung is greater than Ttable which means that this study simultaneously and partially has a significant effect in increasing employee job satisfaction in a company.